JOOX Application as a Media to Improve Students’ Pronunciation - Ari Astutik; Nur Hidayat; Indah Rosyida (Kontribusia : Research Dissemination for Community Development, 2019)
The newest students in university often have difficulty with pronunciation in English. This article is based on the study on students’ pronunciation of Wijaya putra Surabaya University in the first semester. The purpose of this study is to improve the sudents’ pronunciation achievement by using Joox as a media. The subjects were 15 students of wijaya Putra University in the first semester. The data of the study were collected by interview, observation and test. The design of this study was classroom action research which consist of planning, acting, observing and reflecting. In analyzing the data, researcher compared the result of all instruments (interview, observation and test) and concluded it. The result showed that Jooox had positive effect to improve students’ pronunciation achievement.